Návrh vzorků z FDM 3D tištěného materiálu pro materiálovou zkoušku - Strouhal, Jakub (České vysoké učení technické v Praze, 2025)
Teoretická část práce obsahuje úvod do FDM metody 3D tisku a ortotropních materiálů. Popisuje metodu FDM 3D tisku a mechanické vlastnosti tištěných dílů. Dále jsou popsány mechanické vlastnosti, pevnostní kritéria a materiálové konstanty ortotropních materiálů. V práci jsou popsány mechanické zkoušky pro tyto konstanty. V praktické části jsou navrženy vzorky pro tahovou zkoušku vyráběné FDM 3D tiskem pro tři tiskové směry. Tyto vzorky jsou následně testovány na trhacím stroji a jsou u nich vyhodnocené meze pevnosti v tahu, moduly pružnosti v tahu a Poissonova čísla.

Theoretical part of this masters thesis introduces FDM 3D printing process and orthotropic materials. It also outlines the problems associated with this type of printing process, mainly the differences in strength depending on the orientation of the print. Furthermore, it addresses failure criteria and mechanical constants of orthotropic materials. The thesis describes mechanical tests for these constants. The practical part of this thesis consists of design and print parameters of specimens for tensile testing for three different printing orientations. These specimens are tested using a tensile testing machine, and their tensile strengths, elastic moduli, and Poissons ratios are evaluated.
Design of specimens from FDM 3D printed material for material test
Keywords: 3D Tisk; tahová zkouška; FDM; plast; 3D Printing; tensile test; FDM; plastic